1995
DOI: 10.1002/adma.19950070505
|View full text |Cite
|
Sign up to set email alerts
|

The primary steps in photography: Excited J‐aggregates on AgBr Microcrystals

Abstract: The primary process in the photographic emulsion is interfacial electron transfer. The electron is transferred from the excited state of a dye species to empty electron acceptor states in silver bromide. There have been no detailed measurements of the rate constants of this commercially important process. The fluorescence decay curves of thiocarbocyanine dye (see figure) yield these rate constants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…This effect was demonstrated by using cylindrical microcavities filled with colloidal solution of dye and Ag NPs [28,29], or by suspending an optical fiber with an attached microsphere into a solution of the same composition [30]. Adsorption of J-aggregates on silver or silver halide particles (such as AgBr) is of great importance in photographic science and has been studied by many groups [31].…”
Section: Pl Enhancement In a Hybrid Layer Of J-aggregates And Ag Nanomentioning
confidence: 99%
“…This effect was demonstrated by using cylindrical microcavities filled with colloidal solution of dye and Ag NPs [28,29], or by suspending an optical fiber with an attached microsphere into a solution of the same composition [30]. Adsorption of J-aggregates on silver or silver halide particles (such as AgBr) is of great importance in photographic science and has been studied by many groups [31].…”
Section: Pl Enhancement In a Hybrid Layer Of J-aggregates And Ag Nanomentioning
confidence: 99%
“…[1] The photographic industry has relied on the photochemical reactivity of silver and silver halide nanoclusters. [2] Since the 1980s both experiment and theory have shown that the electronic properties of semiconductors on the~1±10 nm scale are governed by quantum mechanical considerations, and thus 1±10 nm diameter spheres of semiconductors are known as quantum dots. [3,4] Fundamentally, the light that is absorbed and emitted by semiconductor nanoparticles are tunable by nanoparticle diameter because the photogenerated electron±hole pair has an exciton diameter that is on the 1±10 nm scale.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent several reports, AgBr might serve as stable and active cocatalyst under visible irradiation by coupling with other proper nanosized materials, such as TiO 2 [15] and Ag [21], which mainly depends on the photogenerated charge transfer between the formed nanoheterostructured composites. To construct AgBr-TiO 2 nanoheterostructured composite, the traditional chemical precipitation in the water system is often employed by using cetyltrimethyl ammonium bromide (CTAB) as bromine sources [13,18]. However, it is difficult to control size and morphology of AgBr, and the produced AgBr and TiO 2 could not be connected effectively, even similar to that of the mechanical mixing preparation, obviously influencing the charge transfer.…”
Section: Introductionmentioning
confidence: 98%
“…Undoubtedly, silver bromide (AgBr) has been used as an attractive small bandgap semiconductor because of its unique lightsensitive, suitable band potentials to produce hydroxyl radicals, and ionic transport properties [17][18][19][20]. In general, pure AgBr is unstable under light irradiation since its photogenerated electrons are easily captured by the Ag + , which greatly affects its practical applications [17,19,20].…”
Section: Introductionmentioning
confidence: 99%